Pemahaman Identitas Moral dalam Meningkatkan Kemampuan Pengambilan Keputusan Etis bagi Para Peserta Didik Pendidikan Agama Kristen - Amos Winarto Oei (Reformed Center for Religion and Society, 2016)
ABSTRACT: This article examines whether appealing to learners moral identity makes a significant contribution to their ethical decision making. Moral identity theory and experiment in moral psychology will be used as a source to be reckoned with in improving ethical decision making. This is to avoid excessive emphasis on emotions, environment and knowledge of the rules which did have an impact on one's ethical decision making. The approach used in this article is the quantitative approach. The result showed that the understanding of moral identity can act as an element to boost the ability of ethical decision making. This suggests that religious education which appeals to the learners moral identity can help them to make better ethical decision when complementing the emotional, the environment and the rule-based knowledge approaches. Thus, it is expected that the learners can have good moral character in the future. This moral identity appeal should be widely adopted as a common practice in religious education class. KEYWORDS: moral identity, ethical decision, understanding, cognitive development, religious education.